Respostas

2013-10-23T22:49:36-02:00
A) 2x² + 5x  + 3 = 0
a= 2
b= 5
c= 3
x= -(5) +- V 5² - 4 . 2 . 3
                     2. 2

x = -5 +- V 25 - 24
                    2

x = -5 +- V 1
               2
x' = - 5 + 1  = 6  = 3    
          2         2
x" = - 5 - 1 = - 6 = -3
           2         2

b) 12 + 5. ( 8 - 16 + 4)  - 3²
     12 + 5 . ( 12 - 16 )  - 9
       12 + 5 . - 4 - 9
          12 - 20 - 9
             12 - 39 = - 27

c) - 5 + ( - 3 . 8 ) : 3 - 2
    - 5 + ( - 24)  : 3 - 2
     - 5 - 24 : 3 - 2
        - 5 - 8 - 2
           - 15